2010
DOI: 10.1007/s10681-009-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of simple sequence repeat markers to genotype Florida strawberry varieties

Abstract: Simple sequence repeats (SSRs or microsatellites) are frequently used as a robust, rapid, and relatively inexpensive means of genotyping. Recent reports in cultivated strawberry (Fragaria 9 ananassa) have identified a widely applicable set of SSRs that permits discrimination of closely-related genotypes. In the present study this same set of SSRs is analyzed in cultivars commonly grown in the state of Florida, as well as advanced breeding selections from the University of Florida program. Nine primer pairs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
(54 reference statements)
1
21
1
Order By: Relevance
“…This primer pair was also the most informative by Honjo et al (2011). According to the number of alleles in this study, the primer pairs ARSFL-009 (20), ARFSL-010 (16) and ARFSL-011 (17) were highly informative also and the number of obtained alleles was higher as compared to the studies of Dangl et al (2007) and Brunings et al (2010), where 26 and 45 genotypes were investigated, …”
Section: Methodssupporting
confidence: 42%
See 2 more Smart Citations
“…This primer pair was also the most informative by Honjo et al (2011). According to the number of alleles in this study, the primer pairs ARSFL-009 (20), ARFSL-010 (16) and ARFSL-011 (17) were highly informative also and the number of obtained alleles was higher as compared to the studies of Dangl et al (2007) and Brunings et al (2010), where 26 and 45 genotypes were investigated, …”
Section: Methodssupporting
confidence: 42%
“…Dangl et al (2007) suggested using the primer ARSFL-009, followed by primers ARSFL-010 and ARSFL-011 for cultivar identification according to their highest number of alleles and unique peak profiles. The primer pair EMFv-104 distinguished 36 genotypes in this study and was most informative in the study of Brunings et al (2010) as well with the ability to distinguish 24 genotypes. The least informative primer pairs in this study were EMFax-381827 and EMFv-125 as both were able to distinguish only 12 genotypes.…”
Section: Characterization Of Strawberry (Fragaria × Ananassa Duch) Cmentioning
confidence: 82%
See 1 more Smart Citation
“…In the cultivated strawberry, the SSR markers selected for genotyping by Govan et al (2008) were tested for their reproducibility in two other laboratories (Brunings et al, 2010). Although Govan et al (2008) had used multiplex PCR, Brunings et al (2010) examined the signals detected by each primer pair individually.…”
Section: ) Genotyping Of Various Cultivarsmentioning
confidence: 99%
“…Although Govan et al (2008) had used multiplex PCR, Brunings et al (2010) examined the signals detected by each primer pair individually. The comparison of allele sizes of common cultivars detected in different laboratories revealed some discrepancies, including missing or additional signals, and 1-2 bp shifts, as shown in grapes.…”
Section: ) Genotyping Of Various Cultivarsmentioning
confidence: 99%